The action for the (propagating) torsion and the limits on the torsion parameters from present experimental data - Belyaev, A. S. [UNESP]; Shapiro, Ilya L. (Elsevier, 1998)
Starting from the well established form of the Dirac action coupled to the electromagnetic and torsion field we find that there is some additional softly broken local symmetry associated with torsion. This symmetry fixes the form of divergences of the effective action after the spinor fields are integrated out. Then the requirement of renormalizability fixes the torsion field to be equivalent to some massive pseudovector and its action is fixed with accuracy to the values of coupling constant of torsion-spinor interaction, mass of the torsion and higher derivative terms. Implementing this action into the abelian sector of the Standard Model we establish the upper bounds on the torsion mass and coupling. In our study we used results of present experimental limits on four-fermion contact interaction (LEP, HERA, SLAC, SLD, CCFR) and TEVATRON limits on the cross section of new gauge boson, which could be produced as a resonance at high energy pp̄ collisions. © 1998 Elsevier Science B.V. All rights reserved.